2011
DOI: 10.1007/s00213-011-2532-9
|View full text |Cite
|
Sign up to set email alerts
|

The acute effects of 3,4-methylenedioxymethamphetamine and d-methamphetamine on human cognitive functioning

Abstract: Further research into the acute effects of amphetamine preparations is necessary to further quantify the acute disruption of aspects of human functioning crucial to complex activities such as attention, selective memory, and psychomotor performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…In particular, use of both MDMA and MA has been associated with neurotoxicity and clinical studies have raised the possibility of adverse effects on cognition, learning and memory (e.g., Baicy & London, 2007; Homer, et al, 2008; McCann, et al, 2008; Nulsen, et al, 2010; Scott, et al, 2007; Stough, et al, 2012). In contrast however, some stimulant drugs are used to improve cognitive functioning in disorders such as ADHD and have been shown to produce cognitive enhancement following acute administration to healthy humans in laboratory settings (Barch & Carter, 2005; Hart et al, 2008; Kirkpatrick et al, 2012).…”
mentioning
confidence: 99%
“…In particular, use of both MDMA and MA has been associated with neurotoxicity and clinical studies have raised the possibility of adverse effects on cognition, learning and memory (e.g., Baicy & London, 2007; Homer, et al, 2008; McCann, et al, 2008; Nulsen, et al, 2010; Scott, et al, 2007; Stough, et al, 2012). In contrast however, some stimulant drugs are used to improve cognitive functioning in disorders such as ADHD and have been shown to produce cognitive enhancement following acute administration to healthy humans in laboratory settings (Barch & Carter, 2005; Hart et al, 2008; Kirkpatrick et al, 2012).…”
mentioning
confidence: 99%
“…Thirteen studies ( n = 240) 125 , 127 , 129 , 130 , 135 , 137 , 140 , 141 , 144 , 150 153 investigated the effects of acute MDMA exposure on executive functioning, utilizing 14 different tasks. The majority of these studies 125 , 127 , 129 , 130 , 135 , 137 , 144 , 150 153 showed no significant effect of MDMA on fourteen tasks, while four studies 130 , 140 , 141 , 152 reported impaired performance across four tasks.…”
Section: Resultsmentioning
confidence: 99%
“…Thirteen studies ( n = 270) 21 , 124 , 125 , 127 , 128 , 133 , 135 , 141 , 144 , 147 , 153 155 assessed the effects of MDMA on attention using 18 different tests. The majority of these studies 21 , 124 , 125 , 127 , 128 , 133 , 141 , 144 , 147 , 153 155 found no effect of MDMA on attentional performance across 17 measures, while four studies 125 , 135 , 141 , 153 reported impaired attention in four tasks.…”
Section: Resultsmentioning
confidence: 99%
“…They assessed the effects of an acute dose of methamphetamine on car driving skills in a laboratory simulator (Stough et al , ). In previous studies, they have found deficits with MDMA and amphetamine, and these latest findings are part of an ongoing series (Stough et al , , ; Silber et al , ). The social drug nicotine has mild stimulant properties, but a complex and multi‐factorial relationship with stress.…”
mentioning
confidence: 82%